2012
DOI: 10.1057/eej.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Civil War, Ethnicity, and the Migration of Skilled Labor

Abstract: We investigate the impact of civil war on high skilled emigration rates to the OECD over the period 1985-2000. Controlling for economic and institutional characteristics of source countries, we find that civil war increases high skilled emigration by about 5 percent on the average. However, the nature of conflict matters: While brain drain from countries with ethnic conflict is about 6-8 percent greater on average than it is from countries without conflict, brain drain from countries with nonethnic conflict is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…It has been suggested that ethnic civil wars should lead to greater high-skilled emigration in both theory and empirics (Bang and Mitra, 2013). We show through a simple conceptual 7 We ran a regression with country fixed effects, which is presented as Appendix Table A5.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that ethnic civil wars should lead to greater high-skilled emigration in both theory and empirics (Bang and Mitra, 2013). We show through a simple conceptual 7 We ran a regression with country fixed effects, which is presented as Appendix Table A5.…”
Section: Discussionmentioning
confidence: 99%
“…The Polity Index ranges from -10 to 10, where -10 to -6 indicates an autocracy, -5 to 5 an anocracy, and 6 to 10 a democracy. Bang and Mitra (2013), is a dummy that takes the value of 1 if there has been an intrastate war in the past five years in the country and 0 otherwise, and is defined according to the UCDP data. Geography controls include the median latitude and median longitude of each country, as well as a dummy variable for whether the country is landlocked or not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations